Early empathy development: Concern and comforting in 9- and 18-month-old infants from Uganda and the UK - Carlo Vreden; Joanna C. Buryn-Weitzel; Santa Atim; Ed Donnellan; Maggie Hoffman; Eve Holden; Michael Jurua; Charlotte V. Knapper; Nicole J. Lahiff; Sophie Marshall; Josephine Paricia; Bahar Tuncgenc; et al. (PLoS ONE, 2025)
Empathy, the capacity to share and understand others’ emotional states, is important for navigating our social lives, yet its development in infancy remains poorly understood. Moreover, most research on empathy development has been biased towards Western populations, which are not representative of global diversity. Using a cross-cultural longitudinal design, this study investigated how infants at 9 and 18 months sampled from Uganda (N = 44, 24 female) and the UK (N = 49, 24 female) develop empathic concern and comforting. Infants watched an adult (mother or experimenter) pretend to injure themselves and the infants’ concerned facial expression and comforting behaviours towards the injured individual were recorded. By 9 months of age, infants at both sites exhibited evidence of facial expressions of concern and onset of comforting behaviour. The likelihood of comforting at both sites increased by 18 months. Results were overall similar at both sites, but we found some site level variation in tendencies to offer comfort spontaneously, with infants in Uganda being more likely to comfort after an explicit cue of need than infants in the UK. Overall, results highlight early onset of empathy development in infancy, with similar developmental trajectories in two sites, despite differences in socio-cultural environment.